25 Years of Adam Mickiewicz University Research at Çatalhöyük (Türkiye) - Filipowicz, Patrycja; Hordecki, Jędrzej; Marciniak, Arkadiusz (Folia Praehistorica Posnaniensia, 2025)
This article presents an overview of 25 years of research conducted by the Adam Mickiewicz University team at Çatalhöyük, Türkiye, focusing on the period from 2014 to 2025. The authors highlight the Polish mission’s significant contributions to understanding both the Neolithic and post-Neolithic occupation of one of the most extensively studied prehistoric sites in Anatolia. The research, carried out in multiple excavation areas – including the TP, TPC, and East Areas – has enabled the construction of a complete stratigraphic sequence for the East Mound, revealing complex architectural developments, burial practices, and material culture spanning from 7100 to 5950 BCE. Significant discoveries include large, multiphase Neolithic buildings, richly decorated interiors, and exceptional anthropomorphic figurines. The Polish mission has also uncovered evidence of later, post-Neolithic occupation, offering new insights into the longterm settlement history of the Konya Plain. The article situates these findings within the broader context of recent advances in Anatolian archaeology, emphasizing the interconnectivity of Çatalhöyük with neighboring sites and regions. The Polish mission’s work has not only deepened scholarly understanding of Çatalhöyük’s local dynamics but also contributed to regional and methodological developments in the study of Anatolia’s prehistoric and early historic periods.